Investigation into alternative financing models for SMEs in Zimbabwe, Mashonaland Central Province - Sherpherd Chaparadza; Simbarashe Mhazo; Nhamo Hove (goodwood publishing, 2025)
Purpose: This research focused on investigating alternative financing instruments for SMEs in the province. This is in view of the fact debt financing has failed to support anticipated growth in the sector as a result of the associated costs. Research Methodology: A case study research design was used for the Mashonaland Central Province. The province's eight (Aziz & Abbas) districts—Bindura, Guruve, Mazowe, Mbire, Mt. Darwin, Muzarabani (Centenary), Rushinga, and Shamva—make up the research population for this study. Since financing is at the core of their viability issues, the study sample, which consists of the province's SMEs, was selected to learn more about how they operate and how they can finance their operations in a sustainable way. 2021 secondary data gathered from these districts were used in the study. This is a secondary study in which Excel-based methods were used to analyze data from the target population. Results: Data analysis shows that unemployed people are absorbed in three sectors: SMEs, vendors, and cooperatives. Overall, SMEs account for 30%, Vending 61%, and Cooperatives 9% of employment. It can also be noted that approximately 80% of SMEs in the province are generally engaged in transport, retail trading, flea markets, and home industries. Conclusions: Adopting asset-based lending and factoring models offers a viable alternative to traditional debt financing for SMEs in Mashonaland Province, supporting sustainable and inclusive economic growth while addressing the sector's need for stable working capital. Limitations: The study is limited to Mashonaland Central province; hence, the results may not be applicable in locations with different environments. Contribution: The study concludes that the SMEs sector in the province is a low-risk and low-return enterprise run on a subsistence basis aimed at maintaining an adequate working capital base. Based on these observations, the study recommends that an asset-based lending model or a factoring model be adopted. These financing models are sound enough to support sustainable and inclusive economic growth based on circular economic principles. This is a clear break from the debt financing model, which has presented a number of challenges over the years. To this end, there is a need for the government and other stakeholders to develop educational campaigns that ensure that SMEs appreciate the operations and importance of these new concepts in business financing so that there is inclusive adoption.